Local dynamics of uniformly quasiregular mappings - Hinkkanen, Aimo; Martin, Gaven J.; Mayer, Volker (Mathematica Scandinavica, 2004)
We investigate local dynamics of uniformly quasiregular mappings, give new examples and show in particular that there is no quasiconformal analogue of the Leau-Fatou linearization of parabolic dynamics.